Old Babylonian Images of Violence in Official and Popular Media - Battini, Laura (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2018)
From the first half of the 2nd millennium BC a numerous images of violence are known, despite the usual emphasis by scholars on the ‘peaceful’ appearance of kings of this period. Second millennium was a decisive epoch in which some important changes in the representation of violence were induced, compared to the 3rd millennium BC. These changes influenced the representation of violence in the following centuries.